Abordagens participativas para o design: metodologias e plataformas sociotécnicas como suporte ao design interdisciplinar e aberto a participação - Silva, Nivaldo Aureo Nascimento da (2012)
There is no area of contemporary life where design is not a significant factor in shaping human experience. Such power demands design to move beyond its traditional disciplines, assuming responsibility for larger issues, at the system level, that comes from the very massive use of its products. To meet these challenges, design stretches towards other areas of knowledge, exploring its integrative discipline potential to promote creativity and innovation among interdisciplinary groups. This dissertation results of a research over the possible shapes of integration between design and non designers, based on authors Clay Spinuzzi and Elizabeth Sanders, that present us participatory design, John Chris Jones, Tim Brown and Richard Buchanan, from design thinking, and a case study that investigates how such collaboration takes place when supported by networked IT. The research revealed that collaboration can happen in two ways. One brings the non designer to participate in design projects which they are to be beneficiaries. The other delivers design ways of thinking and working to be applied in other areas as a tool for creativity and innovation. Both can benefit from using digital media to amplify collaboration, provided there is a process aware management directing contributions. One way or another, design grows as integrative discipline and tool for innovation. And designers learn a new role, as facilitator of interdisciplinary projects of any kind